2018
DOI: 10.1111/1556-4029.13770
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Storage and Additives on Postmortem HbA1c Measurements

Abstract: HbA1c is used in forensic toxicology to identify undiagnosed diabetes mellitus (DM) and those with poor glycemic control prior to death. HbA1c is typically measured in whole blood collected in tubes containing ethylenediaminetetraacetic acid (EDTA). The effect of other additives, including sodium fluoride (NaF), is unclear. Furthermore, the assessment of short- and long-term stability of HbA1c has produced conflicting results. In this study, we collected paired postmortem blood samples in EDTA and NaF tubes (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…A small pilot study on three diabetic and three non-diabetic samples evaluated the stability of HbA1c in EDTA, heparin, citrate and fluoride and found no significant changes when sample was stored at -4C for seven days [7]. Another study found no significant difference in HbA1c or its stability between parallel post-mortem samples collected in EDTA and sodium fluoride vacutainers and stored at 4C [8].…”
Section: Introductionmentioning
confidence: 99%
“…A small pilot study on three diabetic and three non-diabetic samples evaluated the stability of HbA1c in EDTA, heparin, citrate and fluoride and found no significant changes when sample was stored at -4C for seven days [7]. Another study found no significant difference in HbA1c or its stability between parallel post-mortem samples collected in EDTA and sodium fluoride vacutainers and stored at 4C [8].…”
Section: Introductionmentioning
confidence: 99%